Fifth grade students’ difficulties in solving addition of fractions - Novika Oktasari; Syahrilfuddin Syahrilfuddin; Zetra Hainul Putra (Master of Elementary Education, University of Riau, 2022)
Fractions have been applied in daily life and become a prerequisite in learning mathematics, therefore students have to mastered fractions. Many studies state that learning fractions classified as a difficult topic including addition of fraction. The aim of this study was to determine fifth grade’ difficulties in solving fraction addition problems, and to determine factors that cause their experiencing difficulties in learning addition of fractions. The method of this study was a mixed method. The participants were 29 fifth grade students from a public elementary school in Pekanbaru, Riau province, Indonesia. The results showed that many students got difficulties in solving the tasks. The study also showed that the difficulties were experienced by studens in completing addition of fractions including mastering the concept of addition of fractions with 71.43% error. The students were not mastering the prerequisite knowledge of multiplication with 47.29% error and was not able to complete problem solving tasks of adding fractions with 42.53% error. The factors that cause students experiences the difficulties in completing adding fractions are the lack of students’ motivation, students were low on interest of learning mathematics since they assume that mathematics is a difficult subject.